Ekxpansi pengeluaran pemerintah dan responsivitas sektor swasta - Kuncoro, Haryo (Economic Journal of Emerging Markets, 2016)
Any government plays an important role in an economy. The role us presented by both its revenue and expenditure. The net difference of the revenue and expenditure, therefore, determines the type of the revenue and expenditure, therefore, determines the type of fiscal policy implementation.